The Effects of Online Mindfulness-Based Intervention on Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder Symptoms: A Randomized Controlled Trial With 3-Month Follow-Up - Dumarkaite, Austeja; Truskauskaite-Kuneviciene, Inga; Andersson, Gerhard; Kazlauskas, Evaldas (Frontiers in Psychiatry, 2022)
Objectives Mindfulness-based interventions have recently been shown to be a promising option for treating posttraumatic stress. The current study aimed to investigate the effects of an online mindfulness-based intervention on ICD-11 posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) symptoms at a 3-month follow-up. Methods An RCT design with three measurement points (pre-intervention, post-intervention, and 3-month follow-up) was used to investigate the effects of an 8-week online mindfulness intervention. In total, 53 traumatized young adults (Mage = 23.21, SDage = 2.81; 84.9% female) participated in the study: 17 in the intervention group and 36 in the waiting list control group. Results Intervention group and waiting list control group comparison revealed that the intervention was effective for reducing CPTSD disturbances in self-organization symptoms (d = −0.84 [−1.44; −0.24]), specifically, negative self-concept (d = −0.66 [−1.25; −0.07]) and disturbances in relationships (d = −0.87 [−1.47; −0.27]), at 3-month follow-up. There were no between-group effects for PTSD symptoms from pre-test to follow-up. Conclusion This is one of the first RCT studies to report follow-up effects of an online mindfulness-based intervention for ICD-11 PTSD or CPTSD symptoms. Our study yielded that the effects of mindfulness-based internet intervention on CPTSD symptoms tend to retain over time. Trial Registration This study was registered with ClinicalTrials.gov (NCT number: NCT04333667; https://clinicaltrials.gov/ct2/show/NCT04333667). Registered April 3, 2020.